EL LIDERAZGO SITUACIONAL Y EL PODER - Begazo Villanueva, José Domingo (2011)
It can be said that leadership is the skill set that an individual has to influence a group of people, making this group work with enthusiasm in achieving common goals. Is defined as the ability to take initiative, manage, hold, promote, encourage, motivate and evaluate a group or team. In business management leadership is the exercise of executive activity in a project effectively and efficiently, whether personal or institutional management (within the organization’s administrative process).